Bentuk-Bentuk Deiksis Dsalam Novel Ziarah Karya Paulo Coelho's (Kajian Pragmatik): Forms of Deiksis in Paulo Coelho's Novel Pilgrimage (PRAGMATIC STUDY) - Effrem Warung; Monika Sentia (Aliterasi: Jurnal Pendidikan, Bahasa, dan sastra Indonesia, 2022)
Deixis is closely related to the context of speech or speech events that are related to speech interpretation and is very dependent on the context of the speech itself. The problem studied in this research is the forms of deixis contained in the novel Ziarah by Paulo Coelho. This type of research is included in qualitative research, using a qualitative descriptive approach. The research data are in the form of excerpts of sentences containing elements of deixis, while the source of the data for this research is the novel Ziarah by Paulo Coelho Published by PT. Gramedia Pustaka Utama in 2017 with a total of 264 pages. The data collection method used the reading method accompanied by note-taking techniques. The purpose of this study is to describe the forms of deixis contained in the novel Ziarah by Paulo Coelho. The results showed that the forms of deixis in the Ziarah novel were in the form of personal deixis which was divided into the first person deixis manifested in the form of the singular first-person pronouns, namely the word Aku and the plural first-person pronouns namely kami, Kita. The second person deixis is manifested in the form of a singular second-person pronoun, namely you, you, mu. Third-person deixis is manifested in the form of third-person singular pronouns, namely he, she, his, and the plural third-person pronouns, namely they. Place deixis is expressed in the form of the words in, too, from there, here. Time deixis is manifested in the form of words now, yesterday, earlier. Discourse deixis is manifested in the form of the word, old woman, quote. Social deixis is manifested in the form of the words The Guru, Guide, Pilgrim. In the novel Ziarah, the deixis that often appears or is often used is person deixis.